Parents Economic Efforts in the Discourses of Chilean Children: Ethical Reflexivity and Reciprocal Care - Vergara-Del Solar, A (Policy Press, 2020)
This article, written from the perspective of Childhood Studies, questions the image, common in the press and daily life, of childhood as remote from the world of work and the economy. It also challenges the view of children as being immoderate in matters of family expenditure. Two discursive studies of Chilean children reveal instead a complex ethical reflexivity in how they think about the economic efforts of parents, whom they see as overwhelmed by work, economic and care responsibilities and as deserving their understanding and support. We conceptualise these concerns expressed by the children as forms of parent-child reciprocal care, and as ways of upholding cultural images of being a good parent and being a good son or daughter. The personal and economic burden that children perceive in parents is linked to conditions arising from neoliberalisation processes such as those occurring in Chile, and to the exercise of intensive parenting in these contexts. © Policy Press 2020